Strategi Mengoptimalkan Pesantren Berkemajuan pada era pandemi Covid-19 di Lingkungan Persyarikatan Muhammadiyah Bandung - Supriatna, Inding Usup (Bayani, 2021)
This research is a descriptive observation. The purpose of writing this research is to provide insight into the development model of the Muhammadiyah Islamic Boarding School in West Java, especially in Bandung. The selection of the Pesantren was done purposively with the consideration that the Muhammadiyah Islamic Boarding School, because it has declared a progressing Modern Islamic Boarding School, must be maintained and maintained so that it becomes the character and characteristic of the Muhammadiyah Islamic Boarding School. Some examples are mostly taken from ’Aisyiyah Boarding School Bandung, because it has several developments both in terms of curriculum, Human Resources (HR) development, including economic development and business units.